2016
DOI: 10.1140/epjc/s10052-016-4057-1
|View full text |Cite
|
Sign up to set email alerts
|

Quantum corrections to the thermodynamics of Schwarzschild–Tangherlini black hole and the generalized uncertainty principle

Abstract: We investigate the thermodynamics of Schwarzschild-Tangherlini black hole in the context of the generalized uncertainty principle (GUP). The corrections to the Hawking temperature, entropy and the heat capacity are obtained via the modified Hamilton-Jacobi equation. These modifications show that the GUP changes the evolution of the Schwarzschild-Tangherlini black hole. Specially, the GUP effect becomes susceptible when the radius or mass of the black hole approaches the order of Planck scale, it stops radiatin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
59
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(63 citation statements)
references
References 122 publications
(184 reference statements)
4
59
0
Order By: Relevance
“…The incorporation of the GUP to study black hole thermodynamics has been another interesting area of active research [27][28][29][30][31][32][33][34][35][36][37][38]. It has been observed that the GUP reveals a self-complete characteristic of gravity which basically amounts to hiding any curvature singularity behind an event horizon as a consequence of matter compression at the Planck scale [39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…The incorporation of the GUP to study black hole thermodynamics has been another interesting area of active research [27][28][29][30][31][32][33][34][35][36][37][38]. It has been observed that the GUP reveals a self-complete characteristic of gravity which basically amounts to hiding any curvature singularity behind an event horizon as a consequence of matter compression at the Planck scale [39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…By taking into account the effect of GUP, in a curved spacetime, the revised Hamilton-Jacobi equation for the motion of scalar particles can be expressed as [26] g 00…”
Section: Tunneling Radiation Of a Scalar Particle Based On Gupmentioning
confidence: 99%
“…In Refs. [11,12] According to their works, the Hamilton-Jacobi ansatz can be used to describe the tunneling behavior of particles with spin on the horizons of black holes. Hence, the Hamilton-Jacobi ansatz is an effective approach for studying Hawking radiation.…”
Section: Introductionmentioning
confidence: 99%